Banking institutions in Israel - Heth, Meir. (Jerusalem : Maurice Falk Institute for Economic Research in Israel, 1966)
The purpose of this study is to examine the changes which took place in Israel's banking system and in certain aspects of banking activities between 1950 and 1961.
"Published in Hebrew ... in 1963 ... Additional chapter summarizing developments during ... 1962 to 1964 was prepared ... for the English edition."
Bibliographical footnotes.
osc 12/07/2018
Loans
Keywords: Banks and banking